Pain Self-management in Adolescent with Dysmenorrhea - Cherlys Tin Lutfiandini; Tiyas Kusumaningrum; Ni Ketut Alit Armini (Pediomaternal Nursing Journal, 2020)
Introduction: Complaints that often occur are dysmenorrhea that is not harmful but can interfere with comfort and activity. An adolescent who know the proper management of dysmenorrhea can overcome it and have good pain management. The study aimed to analyze pain self-management in adolescents with dysmenorrhoea.Methods: This study used correlational research with a cross-sectional approach. The population in this study were adolescent at Public Junior High School IV Lamongan. The samples were 129 respondents selected by simple random sampling. The inclusion criteria were an adolescent who analyzes dysmenorrhea. The exclusion criteria for this study were not in place due to illness or alpha.  Data was collected using questionnaire self-efficacy, decision making, information support, and pain self-management that had been tested for validity and reliability—test statistics using the Spearman's rho test.Results: The results of the study found a correlation between self-efficacy with pain self-management (p = 0.004; r = 0.24), decision making with pain self-management (p = 0.003; r = 0.26), information support with pain self-management (p = 0.003; r = 0.26).Conclusion: Self-efficacy is a mediator to improve pain self-management optimally to improve quality of life. There are three factors in decision making for pain management in adolescents who experience dysmenorrhea is personal, social, and psychological. Adolescents who have initiatives in finding information about dysmenorrhea have good pain management. It is expected that parents, schools, and health workers provide knowledge to an adolescent who experiences dysmenorrhea to be able to do pain management.